Anthropogenic Sources and Risk Assessment of Heavy Metals in Mine Soils: A Case Study of Bontesso in Amansie West District of Ghana - Douglas Siaw Baah; Emmanuel Gikunoo; Emmanuel Kwesi Arthur; Frank Ofori Agyemang; Gordon Foli; Bennetta Koomson; Philipa Opoku (Journal of Chemistry)
Contamination of the environmental receptors with heavy metals due to mining is a major topical environmental issue in Ghana. This research investigates the possible ecological and human health risks of heavy metal impacts due to mining in the Amansie West District in Ghana. A total of 18 soil samples were taken from the Bontesso illegal mining site in the district and analyzed for the levels of arsenic (As), cadmium (Cd), copper (Cu), nickel (Ni), and lead (Pb) using atomic absorption spectrometry (AAS). From principal component analysis, cluster analysis, and correlation coefficient analysis, the metals are derived from multiple sources, with substantial levels of correlations. Using geo-accumulation index (Igeo), contamination factor (CF), degree of contamination (Cd), pollution load index (PLI), ecological risk index (Er), and noncarcinogenic and carcinogenic risks, respectively, the impacts of As (12.2 mg/kg) and Cd (1.3 mg/kg) are above the WHO stipulated limit. Findings for pollution indices indicate moderate contamination, while HQ < 1 for inhalation and dermal exposure route, except for ingestion which is HQ > 1. Based on the USEPA standard, the carcinogenic risk of the pollutants for humans is higher than the range of 1 × 10−6 to 1 × 10−4. Furthermore, the ingestion route represents the highest contributor to cancer risk with arsenic posing the greatest risk. The results so far suggest that chemical components gradually accumulate and thus emphasize the importance of implementing the necessary mitigation methods to minimize the impacts of illegal mining activities in the study area.